FAKTOR YANG MEMENGARUHI KETAHANAN PANGAN RUMAH TANGGA PEREMPUAN KEPALA KELUARGA (Studi Kasus di Desa Jelu, Kecamatan Ngasem, Kabupaten Bojonegoro) - Febrianti, Yuliana; Yuliati, Yayuk; Sukesi, Keppi (Agros Journal of Agriculture Science, 2024)
Being a female head of household is a challenge. When female heads of households are in a position of poverty, their ability to meet the food needs of the family members they support is also questionable. This will certainly have further implications for the food security of the households under their care. This study aims to determine the factors that influence the food security of female-headed households. This research is a descriptive study using a quantitative approach. The samples in this study were 59 female household heads in Jelu Village, Ngasem Sub-district, Bojonegoro Regency. The analysis used was multiple linear regression using SPSS 24. The results of the linear regression analysis concluded that of the seven independent variables, four variables had a significant effect and three variables had no significant effect. Variables that have a significant effect include age level, type of work, household income, and number of household members. While the level of education, marital status, and the amount of household expenditure had no effect on the food security of female-headed households.